Multifunctional green supramolecular solvents for cost-effective production of highly stable astaxanthin-rich formulations from Haematococcus pluvialis. (1st May 2019) - Salatti-Dorado, José Angel; García-Gómez, Diego; Rodriguez-Ruiz, Violeta; Gueguen, Virginie; Pavon-Djavid, Graciela; Rubio, Soledad
Highlights: A novel combination of supramolecular solvents and nanostructured lipid carriers. Astaxanthin from H. pluvialis powder is extracted, encapsulated and stabilized. Spherical SUPRAS-NLCs of ∼100 nm were obtained. Antioxidant and in vitro ROS scavenging properties are preserved and even enhanced. A remarkable time stability of at least 180 d at 4 °C is guaranteed. Abstract: The interest of food industry to merchandise natural astaxanthin is growing up. However, it confronts scientific and technological challenges mainly related to its poor water solubility and chemical instability. Here, we present a new quick and efficient green process to simultaneously extract, encapsulate and stabilize astaxanthin from Haematococcus pluvialis . The process is based on the hitherto unexplored combination of supramolecular solvents (SUPRAS), nanostructured liquids generated from amphiphiles through sequential self-assembly and coacervation, and nanostructured lipid carriers (NLCs). These novel nanosystems were characterized by means of dynamic light scattering, AFM and cryoSEM, revealing spherical particles of ∼100 nm. Their antioxidant activity was measured by ORAC (20.6 ± 3.9 μM TE) and α-TEAC (2.92 ± 0.58 µM α-TE) assays and their in vitro capacity to inhibit ROS by DHE probe. Results showed that the SUPRAS-NLCs proposed yield high extraction and encapsulation efficiencies (71 ± 4%) in combination with a remarkable time stability (180 d, 4 °C).